Dress with less : consumers’ engagement in Slow Fashion - Rodrigues, Catarina do Deserto Dias (2020)
The Fast Fashion phenomenon has become one of the biggest threats to the environment in current times, consuming abnormal amounts of water and energy, as well as producing tons of greenhouse gases and waste. Slow Fashion has then emerged as the responsible alternative to consumers who started to demand change and raising awareness to Fast Fashion’s harmful impact. This paper studies the online community behind Slow Fashion, looking at its behaviors and attitudes, as well as the main advantages, challenges and complaints consumers have when adopting this lifestyle. Netnography has been chosen to conduct this research, as it is the fittest method. Results show there is high willingness to change habits among consumers and they are starting to adopt strategies to reduce their environmental footprint. As to maintain a positive brand image, companies should focus on tailoring their operational strategies so that they enable might eco-friendly material sourcing and mitigate landfilling and unsold product incineration, therefore appeasing the increasingly demanding consumers. The desired movement requires, however, a structural change in today’s society and Social Marketing and governments are the cornerstones to achieve this circular economy.